Characterization of Rhizosphere Microbial Communities for Disease Incidence and Optimized Concentration of Difenoconazole Fungicide for Controlling of Wheat Dwarf Bunt - Jia, Huanyu; Muhae-Ud-Din, Ghulam; Zhang, Han; Zong, Qianqian; Zhao, Sifeng; Guo, Qingyuan; Chen, Wanquan; Gao, Li (Frontiers in Microbiology, 2022)
Rhizosphere soil microorganisms have great agricultural importance. To explore the relationship between rhizosphere microorganisms and the disease incidence, and to optimize the concentration of difenoconazole fungicide for the control of wheat dwarf bunt, caused by Tilletia controversa Kühn, the rhizosphere microorganisms were characterized based on sequencing methods. We found that the disease incidence correlated with the relative abundance of some microbial communities, such as Acidobacteria, Nocardioides, Roseiflexaceae, Pyrinomonadaceae, and Gemmatimonadaceae. Actinobacteria showed significant differences in the infected soils when compared to the control soils, and the relative abundance of Acidobacteria, Pyrinomonadaceae, Gemmatimonadaceae, and Saccharimonadales populations was distinctly higher in the T. controversa-inoculated group than in the control group. The members of Dehalococcoidia, Nitrosomonadaceae, and Thermomicrobiales were found only in T. controversa-inoculated soils, and these taxa may have potential effects against the pathogen and contribute to disease control of wheat dwarf bunt. In addition, for T. controversa-infected plants, the soil treated with difenoconazole showed a high relative abundance of Proteobacteria, Actinobacteria, Ascomycota, Basidiomycota, Mortierellomycota, and Olpidiomycota based on the heatmap analysis and ANOVA. Our findings suggest that the optimized concentration of fungicide (5% recommended difenoconazole) exhibits better control efficiency and constant diversity in the rhizosphere soil.